2013
DOI: 10.1515/jbcpp-2013-0071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro aldose reductase inhibitory potential of alkaloidal fractions of Piper nigrum, Murraya koenigii, Argemone mexicana, and Nelumbo nucifera

Abstract: It may be concluded that the alkaloidal extracts of these plants possess potent aldose reductase inhibitory activity and may be therapeutically exploited in diabetes-related complications associated with increased activity of aldose reductase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Aldose reductase has an important role in the development of long-term diabetic complications because of increased polyol pathway activity. Gupta et al revealed potent aldose reductase inhibitory activity of hydroalcoholic and alkaloidal extracts of N. nucifera (Gupta et al, 2014). The stamens of N. nucifera were examined for their possible inhibitory activity on aldose reductase and isolated alkaloids from the ethylacetate soluble fraction of the methanolic extract demonstrate potent aldose reductase inhibitory activity (Lim et al, 2006;Veeresham et al, 2014).…”
Section: Pharmacological Reportsmentioning
confidence: 99%
“…Aldose reductase has an important role in the development of long-term diabetic complications because of increased polyol pathway activity. Gupta et al revealed potent aldose reductase inhibitory activity of hydroalcoholic and alkaloidal extracts of N. nucifera (Gupta et al, 2014). The stamens of N. nucifera were examined for their possible inhibitory activity on aldose reductase and isolated alkaloids from the ethylacetate soluble fraction of the methanolic extract demonstrate potent aldose reductase inhibitory activity (Lim et al, 2006;Veeresham et al, 2014).…”
Section: Pharmacological Reportsmentioning
confidence: 99%
“…The highest hit with Nelumbo nucifera indicates the commonality between these two crops. Both black pepper and Nelumbo nucifera are dicot and have common polyol‐alkaloid pathways, potent aldose reductase inhibitory activity is found in their alkaloidal extracts (Gupta et al, 2014). Both are medicinal plants and have larvicidal and repellent activity in the methanol and ethyl acetate extracts (Kamaraj et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The same study also showed that the flavanoid of M. paniculata significantly blocked the decrease of superoxide dismutase and glutathione peroxidase and the increase of malondialdehyde levels in diabetic rats. On the other hand, studies with isolated coumarin of Murraya genus, respectively, showed hypoglycemic activity and inhibitory effect on the activity of the enzyme aldose reductase (Gacche and Dhole, ; Gupta et al, ) and on platelet aggregation (Chia et al, ), which are considered to be important causes of diabetic complications.…”
Section: Discussionmentioning
confidence: 99%